Answer :

nyzia

[tex] \frac{7 - \sqrt{} 29} {2} [/tex]

[tex]x {}^{2} - 7x = - 5 \\ x {}^{2} - 7x - ( - 5) = - 5 - ( - 5) \\ x {}^{2} - 7x( - 5) = 0 \\ x {}^{2} - 7x + 5 = 0 \\ x = \frac{ - ( - 7 + \sqrt{( - 7 {) }^{2} - 4 \times 5} }{2} \\ x = \frac{ - ( - 7 + \sqrt{49 - 4 \times 5} }{2} \\ x = \frac{ - ( - 7) + \sqrt{49 \times 20} }{2} \\ x = \frac{ - ( - 7) \sqrt{29} }{2} \\ x = \frac{7 + \sqrt{29} }{2} \\ \frac{ \sqrt{29 + 7} }{2} \\ x = \frac{7 - \sqrt{29} }{2} \\ x = \frac{ \sqrt{29 + 7} }{2} \\ x = \frac{7 - \sqrt{29} }{2} [/tex]

Other Questions